INVESTIGATING STUDENTSâ DIFFICULTIES IN WRITING USING SIMPLE PAST TENSE: A Descriptive Study Of The Eighth Grade Students In Mts. Muhammad Basiuni Imran Sambas In The Academic Year 2013/2014 - Rizkianto, Rizkianto (West Kalimantan Scholars: Studies on English Language and Education, 2014)
In learning a language, grammar is the most difficult to master because grammar is what most learners think language is. An empirical study was done to 27 students in Mts. Muhammad Basiuni Imran Sambas. A detailed analysis was done to 50 studentsâ answer sheets which produced by the students. The studentsâ answer sheets were collected from 20 items of multiple choice and 30 items changing sentences form in simple past tense. The analysis indicated that many students still have low understanding and also have difficulty when they constructing sentences using simple past tense. Quantitative descriptive analysis indicate that studentsâ difficulty occured chiefly on the use of verb, misplacing the linking verb, using auxiliary in verbal sentence and misuse of singular and plural subject.